The Methamphetamine-Associated Psychosis Spectrum: a Clinically Focused Review - Arunogiri, S.; McKetin, Rebecca; Verdejo-Garcia, A.; Lubman, D. (Springer, 2018)
© 2018 Springer Science+Business Media, LLC, part of Springer Nature. Methamphetamine use is a global concern, and methamphetamine-associated psychosis (MAP) is a particular harm resulting from regular use of the drug that causes significant distress and burden on health and social services. This paper aims to provide a clinically focussed and up-to-date overview of the prevalence, risk factors, and clinical and cognitive features of MAP. The prevalence of MAP ranges between 15 and 30% in recreational settings and up to 60% in some inpatient treatment settings, with up to a third of people with MAP later diagnosed with persistent psychotic disorders. The frequency of methamphetamine use and severity of dependence are the most consistent risk factors for MAP, but other predictors such as genetic vulnerability, a family history of psychotic illness, or trauma also play a role. People with MAP can vary in their presentation, from brief delusional experiences, to persistent psychosis characterised by first-rank symptoms and cognitive impairment. Contemporary conceptualisations of MAP need to incorporate this spectrum of clinical presentations in order to inform clinical decision-making, service provision, and research directions.